Development of the Caecal Microbiota in Three Broiler Breeds - Richards, Peter; Fothergill, Jo; Bernardeau, Marion; Wigley, Paul (Frontiers in Veterinary Science, 2019)
The development of the caecal microbiota plays a role in the metabolism and immune competence of chickens. A detailed understanding of normal succession in the caecal microbiota can inform the use of probiotics and other interventions to optimise the caecal microbiota. The development of the microbiota in caecal mucus and lumen samples from three breeds of broiler chicken (Cobb 500, n = 36; Hubbard JA87, n = 38; and Ross 308, n = 36) was observed between 0 and 42 days post hatch. Chicks were housed in the same room of a climate-controlled, biosecure chicken housing unit. Between 0 and 14 days post hatch, chicks were kept in brooder pens ensuring a mixture of breeds in each brooder. From 22 days post hatch, chicks were removed from the brooders and kept in the same room. DNA was extracted from a pooled sample of caecal mucus and luminal contents from five birds of each breed at 0, 3, 7, 14, 21, 28 and 42 days post hatch. High-throughput Illumina sequencing was performed for the V4 hypervariable region of the 16S rRNA gene. The early caecal microbiota was characterised by poor diversity and dominance by one or two bacterial species. Early colonisers of the caecum included Bifidobacteriaceae, Lachnospiraceae, Bacteroidaceae and Burkholderiaceae with some amplicon sequence variants (ASVs) assigned to Ruminococcaceae. Later colonisers of the caecal microbiota were most apparent from 14 d.p.h and included Ruminococcaceae, Clostridiales vadin BB60 group, Christensenellaceae and Bacillaceae. The caecal microbiota continued to change until 42 d.p.h when the microbiota was characterised by a high abundance of Bacteroidaceae, Lachnospiraceae and Ruminococcaceae. The lumen microbiota was significantly different to the mucus with some ASVs assigned to Lachnospiraceae, Ruminococcaceae, Christensenellaceae and Bacillaceae showing increased abundance in the mucus. ASVs assigned to Bacteroidaceae, Lactobacillaceae and Burkholderiaceae showed a preference for the lumen. Analysis of five caecal mucus samples from each breed at 42 days post hatch showed differences in microbiota composition between Ross and Cobb as well as between Ross and Hubbard. Since performance data was not collected no functional inferences as to the significance of this finding can be made.